Global experiences in vocational training in Primary Education: A look at the decadent, operating and emerging trends (Revista Electrónica Calidad en la Educación Superior, 2023)
Resume:Today's world represents an unprecedented scenario for educational change that demands new skills and knowledge to discover in the professional training of primary education; Based on the above, this research focuses on the analysis of the decadent, operating and emerging trends in the training of primary education professionals in seven countries around the world. It is concluded that innovative trends point towards the enrichment of the relationship between pedagogical theory and practice from a totalizing approach in which all disciplines are integrated, while the person in training processes is assumed as part of a triad in which the educational institution, the universities and the ministries of education interact permanently.